2020
DOI: 10.5194/acp-20-3459-2020
|View full text |Cite
|
Sign up to set email alerts
|

Low-level mixed-phase clouds in a complex Arctic environment

Abstract: Abstract. Low-level mixed-phase clouds (MPCs) are common in the Arctic. Both local and large-scale phenomena influence the properties and lifetime of MPCs. Arctic fjords are characterized by complex terrain and large variations in surface properties. Yet, not many studies have investigated the impact of local boundary layer dynamics and their relative importance on MPCs in the fjord environment. In this work, we used a combination of ground-based remote sensing instruments, surface meteorological observations,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 76 publications
7
51
1
Order By: Relevance
“…Shupe et al (2011) have analyzed the occurrence and macro-physical properties of Arctic clouds at six observatories, including Ny-Ålesund, and found, for example, that clouds are more persistent at the far western Arctic sites. More detailed analyses of cloud radar observations from Ny-Ålesund (Nomokonova et al, 2019b;Ebell et al, 2020;Nomokonova et al, 2019a;Gierens et al, 2020) partly confirmed results of previous studies, e.g. high a cloud occurrence at Ny-Ålesund in summer and autumn, but also revealed differences.…”
Section: Site Descriptionsupporting
confidence: 87%
“…Shupe et al (2011) have analyzed the occurrence and macro-physical properties of Arctic clouds at six observatories, including Ny-Ålesund, and found, for example, that clouds are more persistent at the far western Arctic sites. More detailed analyses of cloud radar observations from Ny-Ålesund (Nomokonova et al, 2019b;Ebell et al, 2020;Nomokonova et al, 2019a;Gierens et al, 2020) partly confirmed results of previous studies, e.g. high a cloud occurrence at Ny-Ålesund in summer and autumn, but also revealed differences.…”
Section: Site Descriptionsupporting
confidence: 87%
“…To study ice and liquid cloud particles separately, it would also be desirable to deploy ice-selective inlets (e.g. Mertes et al, 2007;Kupiszewski et al, 2015;Hiranuma et al, 2016) at Zeppelin Observatory in the future; however, long-term deployment and potential artefacts remain a challenge. In addition, detailed and size-resolved chemical composition and volatility measurements of the sampled cloud residuals and the contribution of supermicron particles would help us to better understand the sources and processes related to low-level Arctic cloud formation.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated cloud vertical profiles were used as input for radiative transfer simulations to analyze the impact of different vertical distributions of the cloud thermodynamic phase on the cloud top horizontal variability. ICON-LEM simulations were forced by initial and lateral boundary conditions from the European Centre for Medium-Range Weather Forecasts (ECMWF) Integrated Forecast System (IFS; Gregory et al, 2010). The simulations were preformed in a one-way nested setup with a 600 m spatial resolution at the outermost domain, followed by 300 m resolution and an inner triangular nest of 150 m resolution.…”
Section: Large Eddy Simulation (Les)mentioning
confidence: 99%